How does top management team diversity matter in abruptly dynamic environments? - Chen, Wein-Hong; Liu, Yi-Yuan (Journal of Business Economics and Management, 2018)
This study seeks to investigate how top management team (TMT) diversity as a double-edged sword influences a firm’s resilient performance in abruptly dynamic environments and how TMT group longevity moderates this relationship. Abruptly dynamic environment is characterized by low-frequency, substantial magnitude, and high-degree irregularity of change. Utilizing 168 listed electronics firms in Taiwan as the sample, this study incorporated the context of the 2008 global financial crisis as a naturally quasi-experimental setting and adopted a less investigated performance metric, firm resilient performance, to investigate how the two most researched types of TMT job-related diversity (i.e., educational and functional diversity) influence firm resilience in such environments. The results suggest that in abruptly dynamic environments, TMT job-related diversity negatively influences firms’ resilient performance, and TMT longevity significantly moderates this relationship. This study makes unique contributions to the upper-echelons literature by investigating the effect of TMT diversity in a naturally quasi-experimental setting featuring abrupt environmental dynamism.